Transmural necrosis of the ascending colon secondary to traumatic hemorrhagic shock: A case report - Kenji Aoshima; Tetsuya Yumoto; Tsuyoshi Nojima; Atsunori Nakao; Hiromichi Naito (Elsevier, 2023)
Introduction: Acute mesenteric ischemia is caused by a severe reduction in blood flow to the intestine, eventually resulting in non-occlusive mesenteric ischemia, and less frequently, bowel necrosis, which is associated with high mortality. Case presentation: We report a 10-year-old boy with no past medical history with necrosis of the ascending colon after resuscitation from hemorrhagic shock due to femoral vein injury caused by a bicycle handlebar injury. Contrast-enhanced computed tomography demonstrated hypodense thickening of the ascending colon wall and intrahepatic portal gas. Exploratory laparoscopy demonstrated necrosis of the ascending colon and paralysis of the intestines. Conclusion: Colonic necrosis secondary to hemorrhagic shock in children without evidence of pre-existing cardiovascular disease is extremely uncommon. Lack of familiarity with this condition may cause serious complications. Clinicians must be aware of this disease to promptly diagnose and aggressively treat the condition early.